Stress Levels and Pre-Eclampsia in Pregnancy - Shinta Novelia; Rukmaini; Evi Puspita Sari (KHD Production, 2024)
Tangerang City Hospital still has cases of preeclampsia where in 2022 there will be 5% of preeclampsia cases. Several factors are associated with the incidence of preeclampsia in pregnant women including maternal age, parity, history of hypertension, history of DM, and stress level. This study aimed to determine the relationship between stress levels and the incidence of preeclampsia in pregnant women at Tangerang City Hospital in 2023. This study is an observational analytic study with a case-control design. The population is all pregnant women aged ≥ 20 weeks who visited the RSUD Kota Tangerang during the study. A purposive sampling technique was used to enroll the sample. The research instrument used is the DASS 42 questionnaire to assess stress levels. The relationship between stress levels and pre-eclampsia was analyzed by the chi-square test. The results of the univariate study showed that the majority of pregnant women with normal stress levels (50%) had mild stress (19.4%), moderate stress (14.5%), severe stress (13.9%), and very severe stress (1.9%). The results of the bivariate study showed that there was a significant relationship between stress levels in pregnant women ≥ 20 weeks gestation (p = 0.000) and the incidence of preeclampsia. Pregnant women with mild stress levels are at risk of preeclampsia with an OR of 4.7. It is hoped that pregnant women who experience stress in their pregnancies can accompanied by their families during their pregnancy so that they can reduce the risk of preeclampsia.